Nanoparticle translocation and multi-organ toxicity: A particularly small problem. (June 2019) - Raftis, Jennifer B.; Miller, Mark R.
Graphical abstract: Highlights: Environmental and manufactured nanoparticles share physicochemical properties and could have similar toxicological profiles. Particles in air pollution have effects on many organ systems. Is the same true for manufactured nanoparticles? Recently inhaled nanoparticles were shown to pass into the circulation in man and amass at sites of vascular inflammation. Translocation of nanoparticles into systemic circulation could underlie their toxicity to multiple organs. The authors stress the importance of risk assessment for manufactured nanoparticles that considers multiple organ systems. Abstract: Environmental nanoparticles and manufactured nanoparticles (MNMs) can share many of the same physicochemical properties and, therefore, could have similar toxicological profiles. Inhalation of nanoparticles in air pollution has effects throughout the body; however, the potential for inhaled MNMs to affect multiple organs requires further investigation. The biological mechanisms that link nanoparticles deposition in the lung to their systemic actions remain to be established; however, the passage of nanoparticles into the blood ("translocation") represents a compelling explanation. This article highlights experimental work in animals and man showing that inhaled gold nanoparticles pass into the blood and accumulate at sites of vascular disease. The article discusses the properties of nanoparticles that could influence translocation and highlights some avenues for future research. The processes described have clear relevance, both for MNMs and sources of nanoparticles in air pollution. The authors emphasise the need for risk assessment of potential nanoparticle exposure routes that consider the multiple organ systems.